Application of Carbon Nanotubes (CNTs) for Remediation of Emerging Pollutants - A Review - Jia Hui Chung; Nur Hasyimah; Norelyza Hussein (Tropical Aquatic and Soil Pollution, 2022)
Nanotechnology is currently an upward trend in diverse fields, and therefore, its application will be reviewed in this paper. One of the nanotechnologies which can be used in environmental remediation is carbon nanotube (CNT). Its excellent mechanical and chemical properties allow it to have better achievement in remediating a wide range of organic and inorganic pollutants. CNT can be categorized into two types: single-walled carbon nanotube and multi-walled carbon nanotube. Due to urbanization, various types of pollutants have been released into the environment in great amounts. For instance, estrogen is the hormone generated and released from animals and humans. However, the overconcentration of estrogen affects the physiology of biological life. Besides, pesticides are frequently used by farmers to increase the fertility of the land for agricultural purposes, while heavy metals are commonly found during anthropogenic activities. Long-term absorption of heavy metals into the body tissues will accumulate toxic effects, leading to body system dysfunction. Hence, CNT technologies, including adsorption, membrane filtration, disinfection, hybrid catalysis, and sensing and monitoring, can be applied to remediate these pollutants. However, the application of nanotechnology and CNT faces several challenges, such as production costs, toxicity, ecological risks, and public acceptance. Application of CNT also has pros and cons, such that the lightweight of the CNT allows them to replace metallic wires, but dealing with nano-sized components makes it challenging.